2021
DOI: 10.3390/m1204
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of New 1,2,3-Triazole-Amino Acid Conjugates

Abstract: A multistep synthesis was developed to prepare new 1,2,3-triazole-amino acid conjugates (6 and 7). These compounds contain the diaryl ether moiety and were synthesized via SNAr reaction under mild condition and in good yield. Their structures were confirmed by spectroscopic analyses (HR-MS, NMR, IR). These compounds showed significant antiproliferative activity (>30%) toward the breast MCF7 and liver HepG2 cancer cells lines at <10 µM concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The results showed that at 40 μM, except phenylalanine derivatives DE‐Phe‐OEt 4 c , DE‐Phe‐OH 5 c and DE‐Phe‐NHNH 2 7 c , other compounds showed unsignificant MCF‐7 inhibitory activity (<20 %). This suggests phenylalanine derivatives are more favorable for antiproliferation activity compared to other studied amino acid derivatives (Gly, Val, and Met) and in agreement with our previous study [9] . Among the phenylalanine derivatives 4 c , 5 c , and 7 c , at 40 μM, the least polar ethyl ester containing compound 4 c is the most potent with 54 % inhibitory activity while an equal activity of 36–37 % inhibitory activity was observed for carboxylic acid containing compound 5 c and hydrazide containing compound 7 c .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that at 40 μM, except phenylalanine derivatives DE‐Phe‐OEt 4 c , DE‐Phe‐OH 5 c and DE‐Phe‐NHNH 2 7 c , other compounds showed unsignificant MCF‐7 inhibitory activity (<20 %). This suggests phenylalanine derivatives are more favorable for antiproliferation activity compared to other studied amino acid derivatives (Gly, Val, and Met) and in agreement with our previous study [9] . Among the phenylalanine derivatives 4 c , 5 c , and 7 c , at 40 μM, the least polar ethyl ester containing compound 4 c is the most potent with 54 % inhibitory activity while an equal activity of 36–37 % inhibitory activity was observed for carboxylic acid containing compound 5 c and hydrazide containing compound 7 c .…”
Section: Resultssupporting
confidence: 92%
“…We hypothesized that the DE motif 1 prepared from vanillic acid and 1-fluoro-4-nitrobenzene in our previous study [9] (scheme 1) could be favourable for biological activity. In addition, we chose to conjugate this DE motif to four different natural amino acids 1) glycine for small achiral moiety, 2) valine with aliphatic hydrophobic group, 3) phenylalanine with aromaticity and 4) methionine with flexible chain contanining heteroatom.…”
Section: Design and Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer has life serious threats to global health that causes one out of six life losses in the world. 1 The triazoles derivatives revealed extensively antiproliferative potency against human prostate, 2 breast, 3 liver, 4 lung, 5 bladder 6 and other cancer cells, in drug discovery. Mimicking glycosides, Nerella and co-workers 7 built new1,2,3-triazoles based on carbohydrate molecule that have notable anticancer activity against breast and prostate cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%